Design Museum London - Design Museum (2010)
[Dt.:] Ein führendes Museum für zeitgenössisches Design von Architektur und Mode bis zu Grafik, Produkt- und Industriedesign. - [Engl.:] A leading museum devoted to contemporary design in every form from architecture and fashion to graphics, product and industrial design.